A new triadotypomorphan insect from the Anisian (Middle Triassic), Buntsandstein facies, Spain - López-gómez, J.; Béthoux, O.; Benito, M.I.; De la Horra, R.; Barrenechea, J. F.; Galán, A. B. (Journal of Iberian Geology, 2009)
The species rubra sp. nov., a new triadotypomorphan insect from the Iberian Ranges, is described on the basis of a newly discovered specimen, found in fine grained sandstones of alluvial origin, in the lowermost part of the Eslida Formation (Buntsandstein facies), in the central part of the Iberian Ranges. The occurrence of a triadotypomorphan suggests an Anisian age of the Eslida Formation. The species represents the oldest Mesozoic insect described from Spain, and provides interesting information to better appreciate the process of ecosystems recovery after the Permian-Triassic boundary crisis.